Comparison of the Efficacy of Single or Double Intravesical Epirubicin Instillation in the Early Postoperative Period to Prevent Recurrences in Non-Muscle-Invasive Urothelial Carcinoma of the Bladder: Prospective, Randomized Multicenter Study - TANIDIR, YILÖREN (KARGER, 2010)
Objectives: To investigate the efficacy of single or double epirubicin instillation during the early postoperative period (EPP) in intermediate-risk non-muscle-invasive urothelial cancer. Methods: Patients with primary and solitary or multiple (3 or less) Ta (grade 2-3) or T1 (grade 1-2) tumors were enrolled. Patients were randomized to receive either a single dose of 100 mg epirubicin instillation within 6 h or a second 100 mg epirubicin instillation during the 12th-18th hours after a complete TUR-BT. At the end of the 60-month follow-up period, the available data were statistically analyzed. The end-points of the study were determined as disease-free survival, progression and recurrence rates, time to recurrence, and time to progression. Results: A total of 299 patients from 24 institutions were randomized between January 2002 and June 2004. There were 143 patients from 18 institutions who met the eligibility criteria. The follow-up and disease-free survival periods were 16.9 months and 16 months, respectively. There was no statistical difference in the demographic properties and the end-points between the groups. Conclusions: A single dose of intravesical 100 mg epirubicin chemotherapy during the early postoperative period for primary intermediate-risk non-muscle-invasive urothelial cancer achieved 16 months of mean disease-free survival. A second intravesical epirubicin instillation did not provide any significant benefit. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Bladder cancer, non-muscle-invasive; Intravesical chemotherapy; Epirubicin; Recurrence-free survival; TRANSITIONAL-CELL CARCINOMA; STAGE TA; TRANSURETHRAL RESECTION; CANCER; CHEMOTHERAPY; PROPHYLAXIS; RISK